Penerapan Metode ANP dan BORDA Dalam Sistem Pendukung Keputusan Pendistribusian Zakat Pada Badan Amil Zakat Kota Medan - Nst, Aila Oktavia Abdul; Zufria, Ilka (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The process of collecting and distributing zakat is currently managed by an institution called the Amil Zakat Agency (BAZ) which is spread throughout Indonesia, including in the city of Medan. The Amil Zakat Agency in Medan City is called Baznas Medan City. Medan City Amil Zakat Agency (Baznas) is an amil body that is responsible for the collection, distribution and management of zakat in Medan City. This study applies the ANP and BORDA methods in the zakat distribution SPK at the Medan City Baznas. In producing a decision support system in selecting who is entitled to receive zakat in Medan City using the ANP and BORDA methods. The data obtained will later be used in system development. System development means creating a new system to completely replace the old system or improve the existing system. Selection of Baznas Recipient Candidates in this system will produce a ranking based on ANP and Borda calculations. The SPK at the Medan City Baznas using the ANP and BORDA methods was successfully designed and built based on the terms and conditions set by the relevant parties. This system can make it easier for staff or officers at the Medan City Baznas to select mustahik who are the most appropriate and eligible to receive assistance from the Medan City Baznas. Based on the results of the Black Box test, the features of the Decision Support System for zakat recipients that were built went very well and it can be concluded that each form of this system has met expectations in minimizing errors whether invalid data or errors in data input